1985
DOI: 10.1111/j.1365-2672.1985.tb01712.x
|View full text |Cite
|
Sign up to set email alerts
|

A new apparatus for continuous cultivation of bacterial plaque on solid surfaces and human dental enamel

Abstract: A new apparatus for the continuous cultivation of mono and mixed bacterial plaque on solid surfaces is described. The features are: easy preparation and handling; freedom from technical problems and microbial contamination; self-sufficient for periods of up to 56 d; 12 samples are taken simultaneously; programmable supply inlet. Experiments were performed with Streptococcus mutans C 67-1 for mono bacterial inoculation and in combination with Veillonella alcalescens V-1 for mixed bacterial inoculations. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, the possibility for manipulation of the test specimens during operation or their number per turn has been considered to be very limited for most devices described in the literature or they do not allow for the use of whole tooth specimens [Fontana et al, 2000;Noorda et al, 1985;Tang et al, 2003;Deng and ten Cate, 2004]. According to our knowledge, no reports regarding caries development at marginal gaps of fissure sealants in artificial mouth models are available in the literature written in English.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…However, the possibility for manipulation of the test specimens during operation or their number per turn has been considered to be very limited for most devices described in the literature or they do not allow for the use of whole tooth specimens [Fontana et al, 2000;Noorda et al, 1985;Tang et al, 2003;Deng and ten Cate, 2004]. According to our knowledge, no reports regarding caries development at marginal gaps of fissure sealants in artificial mouth models are available in the literature written in English.…”
mentioning
confidence: 79%
“…Therefore, ventilation of the reaction chamber with a defined gas seems to be a logical consequence. Because the oral cavity is not an anaerobic environment and S. mutans biofilms have been successfully cultivated in artificial mouth models either under aerobic [Dibdin et al, 1976;Noorda et al, 1985] or anaerobic [Schiffner, 1999] conditions, we used commercially available synthetic air with 5% CO 2 in our model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that 'a mixed-culture chemostat is a suitable system for studying the effects of nutrients on microbial populations; however, unlike the 'artificial mouth' system, the chemostat model does not account for the spatial arrangement o f dental plaque' since bacteria are studied in suspension and not as a biofilm on the tooth sur face. Zampatti et al [1994] used S. mutans in a mouth model based on Noorda et al [1985] to test the efficacy of anti plaque agents. Their model involved the use of bovine teeth to study plaque formation, but no attempt was made to study dental caries.…”
Section: Discussionmentioning
confidence: 99%